Vitamin K antagonists in heart disease: Current status and perspectives (Section III) - Caterina, Raffaele De; Husted, Steen; Wallentin, Lars; Andreotti, Felicita; Arnesen, Harald; Bachmann, Fedor; Baigent, Colin; Huber, Kurt; Jespersen, Jørgen; Kristensen, Steen Dalby; Lip, Gregory Y. H.; Morais, Joaõ; Rasmussen, Lars Hvilsted; Siegbahn, Agneta; Verheugt, Freek W. A.; Weitz, Jeffrey I. (Thrombosis and Haemostasis, 2013)
Oral anticoagulants are a mainstay of cardiovascular therapy, and for over 60 years vitamin K antagonists (VKAs) were the only available agents for long-term use. VKAs interfere with the cyclic inter-conversion of vitamin K and its 2,3 epoxide, thus inhibiting γ-carboxylation of glutamate residues at the amino-termini of vitamin K-dependent proteins, including the coagulation factors (F) II (prothrombin), VII, IX and X, as well as of the anticoagulant proteins C, S and Z. The overall effect of such interference is a dose-dependent anticoagulant effect, which has been therapeutically exploited in heart disease since the early 1950s. In this position paper, we review the mechanisms of action, pharmacological properties and side effects of VKAs, which are used in the management of cardiovascular diseases, including coronary heart disease (where their use is limited), stroke prevention in atrial fibrillation, heart valves and/or chronic heart failure. Using an evidence-based approach, we describe the results of completed clinical trials, highlight areas of uncertainty, and recommend therapeutic options for specific disorders. Although VKAs are being increasingly replaced in most patients with non-valvular atrial fibrillation by the new oral anticoagulants, which target either thrombin or FXa, the VKAs remain the agents of choice for patients with atrial fibrillation in the setting of rheumatic valvular disease and for those with mechanical heart valves.
Keywords: Coagulation; oral anticoagulants; vitamin K antagonists; coronary heart disease; atrial fibrillation; artificial heart valves; heart failure